STANDARDISATION OF VRISCHIKAGAD - Joshi , Shreyas S (International Research Journal of Ayurveda & Yoga, 2024)
Authentication and Standardization are the two basic needs of any research. While doing research in Ayurved every one has to authentify and standardize the raw material as well as the final product also. As there are many controversies amongst drugs. So, to overcome this issue Government of India has formulated the Ayurvedic Pharmacopoeia of India (API) stating standards for each drug and Ayurvedic Formulary of India (AFI) stating standards for final product formulations. But Agad(Antidotal/Anti Poisonous) formulations are not included in the AFI and still some addition of drugs are needed in the API also. In this study I have obtained values for such drugs which are not mentioned in the API as well as AFI. Based on the nature of the product or material the relevant tests were used and the values are obtained for Matulung Phal Swaras, Paravat Shakrit and the final product called Vrischikagad. Addition in the API and AFI is a continuous process and in the near future Agad will also get included in the Ayurvedic formulary of India